1999
DOI: 10.1080/00071669987287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ambient temperature on heat increment of feeding and energy retention in growing broilers maintained at different food intakes

Abstract: Zero-activity heat production (HP), body temperature (Tb) and energy retention were measured in growing broilers maintained at 5 ambient temperatures (Ta) (14 degrees , 17 degrees , 22 degrees , 27 degrees and 32 degrees C) and at 5 feeding rates (ad libitum intake and 75%, 50%, 25% and 0% (fasting) of ad libitum). Zero-activity HP increased with decreasing Ta and increasing food intake. However, at 14 degrees C, zero-activity HP in birds fed ad libitum and 75% did not show further increase, but those in birds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The main consequence of exposure to heat is that birds reduce their feed intake (Geraert et al, 1996) in order to diminish metabolic heat production in an attempt to maintain their body temperature (Koh & Macleod, 1999); however, major reduction in energy and nutrient intake may compromise productivity (Leeson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The main consequence of exposure to heat is that birds reduce their feed intake (Geraert et al, 1996) in order to diminish metabolic heat production in an attempt to maintain their body temperature (Koh & Macleod, 1999); however, major reduction in energy and nutrient intake may compromise productivity (Leeson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Drastic decline in feed intake occurs in heat-stressed birds as a physiological response to minimize intrinsic heat production and to maintain the thermal homeostasis, thus bringing down feed efficiency, live weight gain, and survival rates. [11][12][13][14] Lower breast-meat yield and higher carcass-fat deposition are the other deleterious effects of heat stress that lower the economic value of broiler carcasses. 10,11,15 Betaine, the trimethyl derivative of the amino acid glycine, is a naturally occurring compound distributed widely in many plants and animal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Feed intakes of laying hens can vary, depending on metabolizable energy intakes and environmental temperature (North, 1978;Jurgens, 1993). Ad libitum broiler intake varies depending on numerous factors, such as growth rate, diet composition, ambient temperature and corticosterone concentration (Dale and Fuller, 1980;Gous, 1998;Koh and Macleod, 1999;Nasir et al 1999). Dale and Fuller (1980) reported that feed to gain ratios for poultry may also depend upon species, as exotic species such as ostriches and cockerels have been shown to metabolize energy more effi ciently than poultry (Cilliers et al, 1999).…”
Section: Complete Diets and Salmonella Spp Contaminationmentioning
confidence: 99%